Deoxidation in molten steel by liquefied petroleum gas - WANG Hai-jun; WANG Jian-jun; MENG Yu-yong; CHANG Li-zhong; ZHOU Li (工程科学学报)
Oxygen in molten steel was removed with liquefied petroleum gas in laboratory. The results show that it is feasible to use liquefied petroleum gas for deoxidation in molten steel to produce high-carbon and high-quality clean steel with VD vacuum smelting assistance. The deoxidation rate is faster with a mixed gas of argon and liquefied petroleum gas than just using a single gas, the oxygen content decreases more significantly and the rate of increase of the carbon content declines. After deoxidation for 8 min, the velocity of deoxidation decreases, and the oxygen content has no significant declination. At the beginning of deoxidation, the carbon content increases slowly; however, while the oxygen content decreases to a certain level the carbon content rapidly increases. Argon does have effect on stirring molten steel, and lead to having a good dynamic condition to facilitate the removal of hydrogen in molten steel.